Comparative Study of the Actions to Consider in the Process of Conceptual Design from the Engineering and the Product Design [Estudio Comparativo de Las Acciones a Considerar en el Proceso de Diseño Conceptual Desde la Ingeniería y el Diseño de Productos] - Guerrero-Valenzuela, M (Universidad de Tarapaca, 2014)
This article presents a review of the traditional models used to define conceptual design both in the design process and the stages that are part of them. The concordances and differences of the actions and tasks described for the definition of the concept of design, from the perspective of the engineering as opposed to that of the designers, are compared in order to understand how the different procedures for its implementation are addressed. It is shown that the actions carried out from the engineering way of work perspective are precise, descriptive and they are addressed as a matter of routine. Nevertheless, the models reviewed show, from the designe?s point of view, lack of precision and clarity in the development of the conceptual design, thus not enabling for clarification of the tasks and actions aimed to represent the characteristics and physical aspects of the concept, in order to shape the product. It is seen that the functional and morphological dimensions require a better approach, more precision and mutual interaction in the design space. It is also concluded that diminishing the uncertainty in the handling and characterization of conceptual ideas is an important task in the stage of conceptual design. The new methodological approaches and models must be described in the most clear and precise manner in order to optimize and facilitate the making of the design process both in engineering and product design.